2021
DOI: 10.3390/microorganisms9061201
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Profiles and Resistance Genes in Genus Aeromonas spp. Isolated from the Environment and Rainbow Trout of Two Fish Farms in France

Abstract: This study presents the occurrence and abundance of Aeromonas antibiotic-resistant bacteria (ARB) and genes (ARGs) isolated from water, biofilm and fish in two commercial trout farms before and one week after flumequine treatment. Wild (WT) and non-wild (NWT) strains were determined for quinolones (flumequine, oxolinic acid and enrofloxacin), oxytetracycline (OXY), florfenicol (FFN), trimethoprim-sulfamethoxazole (TMP) and colistin (COL), and pMAR (presumptive multi-resistant) strains were classified. Forty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
2
3
1
3
Order By: Relevance
“…In addition, we have also confirmed in the A. veronii strain described here, the presence of the previously described ColE as a plasmid of the qnrS gene [ 45 ]. These results correlate with that described by Hayatgheib et al [ 46 ] on Aeromonas spp. isolated from farmed rainbow trout, and by Yang et al [ 47 ] specifically on A. veronii strains isolated from farmed channel catfish.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we have also confirmed in the A. veronii strain described here, the presence of the previously described ColE as a plasmid of the qnrS gene [ 45 ]. These results correlate with that described by Hayatgheib et al [ 46 ] on Aeromonas spp. isolated from farmed rainbow trout, and by Yang et al [ 47 ] specifically on A. veronii strains isolated from farmed channel catfish.…”
Section: Discussionsupporting
confidence: 93%
“…MAR index was the highest (0.8) for A. veronii strain 6, which also carried all the tested virulence genes. In a recent study, 36% isolates of Aeromonas strains isolated from diseased rainbow trout were found to be multi-antibiotic resistant [77]. In another study, it was found that across a period of ten years, the fish-isolate Aeromonas spp.…”
Section: Discussionmentioning
confidence: 97%
“…The MIC value of enrofloxacin was reported as 0.5 μg/mL for A. sobria , and A. hydrophila isolated from carp [ 16 , 33 , 44 ]. In the samples taken from rainbow trout and environmental strains, the MIC value of enrofloxacin for Aeromonas spp., were found to be 0.008–4 μg/mL [ 44 , 45 ]. In this study, for A. hydrophila and A. sobria isolated from the fish farm, the MIC 50 value was 0.25 and 0.5 µg/mL, respectively, and the MIC 90 values were calculated as 1 µg/mL for both species.…”
Section: Discussionmentioning
confidence: 99%